P198 Prepare-IBD: physician responses to flares and patient adaptation in IBD during the COVID-19 pandemic. (19th June 2022) - Saifuddin, Aamir; Kent, Alexandra; Mehta, Shameer; Hicks, Lucy; Gonzalez, Haidee; Patel, Kamal; Lamb, Christopher; Walker, Gareth; Kennedy, Nicholas; Sebastian, Shaji
Abstract : Introduction: During the uncertainty of the first wave of the COVID-19 pandemic, clinicians had to weigh up the immunosuppressive effect of inflammatory bowel disease (IBD) medications against control of symptoms and disease activity. We sought to explore treatment adaptations and patient outcomes during this period across the United Kingdom. Methods: An observational cohort study was performed, comprising patients who contacted IBD teams for a symptom flare between March – June 2020 in 60 National Health Service trusts. IBD management and 3-month outcomes were compared to a pre-pandemic cohort from January – June 2019 after propensity-matching for age and disease severity. COVID-19 status was based on suspicious symptoms and/or polymerase chain reaction (PCR) positivity, as the former would have influenced real-time IBD decision-making, particularly when PCR testing was less common. Comparisons were performed using Fisher's exact test. Results: In total, 3728 patients in the pandemic (n=1864) and pre-pandemic (n=1864) cohorts were included. The principal findings were reduced systemic corticosteroid prescription during the pandemic in both Crohn's disease (prednisolone: pandemic 199/752, 26.5% vs 263/708, 37.1%; p<0.001) and ulcerative colitis (UC) (prednisolone: pandemic 372/1112, 33.5% vs 470/1156, 40.7%, p<0.001), with increases in poorly bioavailable oral corticosteroids in both Crohn's disease (pandemic 117/752, 15.6% vs 48/708, 6.8%; p<0.001) and UC (pandemic 131/1112, 11.8% vs 60/1156, 5.2%; p<0.001). Ustekinumab (Crohn's disease and UC) and vedolizumab (UC) treatment also significantly increased during the pandemic. Three-month steroid-free remission was similar in both Crohn's disease (pandemic 175/616, 28.4% vs 195/608, 32.1%; p=0.17) and UC (pandemic 312/858, 36.4% vs 404/1006, 40.2%; p=0.095). The 65 patients experiencing a flare and COVID-19 were more likely to have moderate-to-severely active disease at three months compared to those with a flare alone. Conclusions: Despite several treatment adaptations during the pandemic, steroid-free outcomes were comparable to pre-pandemic levels, though patients with a flare and COVID-19 experienced worse outcomes. These findings have implications for IBD management during future waves or pandemics.